2014
DOI: 10.1002/mrd.22332
|View full text |Cite
|
Sign up to set email alerts
|

Auto‐amplification system for prostaglandin F2α in bovine corpus luteum

Abstract: The bovine corpus luteum (CL) is hypothesized to utilize a local auto-amplification system for prostaglandin (PG) F2α production. The objective of the present study was to determine if such a PGF2α auto-amplification system exists in the bovine CL, and if so, which factors regulate it. PGF2α significantly stimulated intra-luteal PGF2α production in all luteal phases, but did not affect PGE2 production. The stimulatory effect of exogenous PGF2α on CL PGF2α production was lower at the early luteal phase. Indomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This auto-amplification loop system for PGF 2α production may aid in the progression towards CL luteolysis. Enzymes such as PTGS2 and PTGFS are known to participate in PGF 2α synthesis [ 56 , 57 ]. Shirasuna et al [ 56 ] confirmed that the mRNA expression of key enzymes of PGF 2α biosynthesis was increased in the bovine CL after PGF 2α treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This auto-amplification loop system for PGF 2α production may aid in the progression towards CL luteolysis. Enzymes such as PTGS2 and PTGFS are known to participate in PGF 2α synthesis [ 56 , 57 ]. Shirasuna et al [ 56 ] confirmed that the mRNA expression of key enzymes of PGF 2α biosynthesis was increased in the bovine CL after PGF 2α treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 and PGF 2α have opposing effects, but it has been suggested that their expression is coordinated to achieve a balance in vivo . It has also been proposed that PGF2α significantly stimulated intra-luteal PGF 2α production in all luteal phases, but did not affect PGE2 production [ 28 ]. PGE 2 rapidly increased TbetaRIII mRNA and protein expression and enhanced TbetaRIII gene promoter activity ctivity, whereas PGF 2α does not [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since leukocytes are known to produce a variety of cytokines including IFNG and TNF [ 38 ], the uterus and macrophages seem to be sources of PGF and INFG. In addition, we described an auto-amplification system for PGF in the bovine CL [ 39 ]. Luteal PGF may also play a role in regulating MMP-1 and TIMP expression during luteolysis.…”
Section: Discussionmentioning
confidence: 99%